551. MK-8591 Does Not Alter the Pharmacokinetics of the Oral Contraceptives Ethinyl Estradiol and Levonorgestrel. (26th November 2018) - Ankrom, Wendy; Jonathan, Daniel; Rudd, Deanne; Zhang, Sandra; Fillgrove, Kerry; Gravesande, Kezia; Matthews, Randolph; Brimhall, Darin; Stoch, Aubrey; Iwamoto, Marian
Abstract: Background: Over 2 million girls and young women are living with HIV, being newly infected at disproportionately high rates. HIV infection adds risks to pregnancy, including vertical transmission and maternal death. Hormonal contraceptives are among the most effective reversible contraceptives, but they have clinically meaningful drug–drug interactions (DDI) with many antiretrovirals (ARV). MK-8591 is a novel nucleoside reverse transcriptase translocation inhibitor (NRTTI) currently in Phase 2 clinical development for treatment of HIV. Unlike many ARVs, MK-8591 is not an inhibitor or inducer of major CYP enzymes and is not expected to alter the pharmacokinetics (PK) of hormonal contraceptives. This clinical study evaluated the DDI of MK-8591 with levonorgestrel (LNG) and ethinyl estradiol (EE) to support use of hormonal contraceptives with MK-8591. Methods: This was an open-label, two-period, fixed-sequence DDI study in 14 healthy, postmenopausal or oopherectomized females aged 50–64. A single dose of LNG 0.15 mg/EE 0.03 mg was given followed by a 7-day washout. MK-8591 20 mg was then dosed once weekly for 3 weeks; a single dose of LNG 0.15 mg/EE 0.03 mg was given concomitantly with the third dose of MK-8591. PK samples were collected for evaluation of LNG and EE levels. Individual values of AUC0-inf and Cmax were natural log-transformed prior to analysis and evaluated separately using a linear mixed effects model with a fixed effects term for treatment. An unstructured covariance matrix was used to allow for unequal treatment variances and to model the correlation between the treatment measurements within each subject. Results: The PK of EE and LNG were not meaningfully altered by co-administration with MK-8591. For the comparison of (MK-8591 + LNG/EE) / (LNG/EE alone), the geometric mean ratios (GMRs) (90% confidence intervals (CIs)) for LNG AUC0-inf and Cmax were 1.13 (1.06, 1.20) and 0.965 (0.881, 1.06), respectively. For EE the GMRs (90% CI) for AUC0-inf and Cmax were 1.05 (0.981, 1.11) and 1.02 (0.971, 1.08), respectively. Co-administration of all three drugs was generally well tolerated. Conclusion: The results of this study support use of hormonal contraceptives in HIV-infected patients receiving MK-8591. Disclosures: W. Ankrom, Merck & Co, Inc.: Employee and Shareholder, Salary. D. Jonathan, Merck: Employee, Salary. D. Rudd, Merck & Co., INC.: Employee, Salary. S. Zhang, Merck & Co, Inc.: Employee, Salary. K. Fillgrove, Merck & Co., Inc.: Employee, Salary. K. Gravesande, Kezia Gravesande: Research Contractor, Salary. R. Matthews, Merck: Employee, Salary. A. Stoch, Merck & Co, Inc.: Employee and Shareholder, Salary. M. Iwamoto, Merck & Co, Inc.: Employee and Shareholder, Salary.